Hubungan Karakteristik Individu Dengan Kelelahan Kerja Pada Nelayan Tradisional Di Dusun Tanah Merah Kecamatan Huamual Belakang Kabupaten Seram Bagian Barat - Sunik Cahyawati; Sahrir Sillehu; Ira Fanty Wakan (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2024)
One of the occupational safety and health (K3) problems that can trigger work accidents is fatigue. Work fatigue is a person's condition where their resilience and efficiency at work decreases. Work fatigue is an important problem to overcome, because work fatigue can cause health conditions to decline which will result in decreased work productivity and work accidents. This study aims to determine the relationship between individual characteristics and work fatigue in traditional fishermen in Tanah Merah Hamlet, Huamual Belakang District, West Seram Regency. This research is quantitative research using a "Cross Sectional" approach. The population in this study were fishermen in Tanah Merah Hamlet, namely 65 people. The sampling technique used total sampling, the sample in this study were all fishermen in Tanah Merah Hamlet, namely 65 people. The instrument in this research is a questionnaire. Based on the results of data analysis from the Chisquare test on the variable age and fishermen's work fatigue, a p value of 0.923 (> 0.05) was obtained, which means there is no relationship between age and fishermen's work fatigue in Tanah Merah Hamlet. Meanwhile, the variable length of work, years of service,type of work and quality of sleep obtained a p value of 0.00 (< 0.05), which means there is a relationship between years of service, length of work, type of work, quality of sleep and work fatigue in traditional fishermen in Tanah Merah Hamlet, Huamual Belakang District West Seram Regency.